Hidradenitis Suppurativa in Kuala Lumpur, Malaysia: A 7-Year Retrospective Review - Moonyza Akmal Ahmad Kamil; Azura Mohd Affandi (Dermatology Research and Practice)
Introduction. Hidradenitis Suppurativa (HS) is a chronic inflammatory skin condition characterized by inflamed nodules, abscesses, sinus tracts, and scarring, which can occur in any skin containing folliculopilosebaceous units. We aim to identify the demographic and clinical characteristics and treatment modalities in patients with HS. Methods. A retrospective analysis involving records of patients diagnosed with HS in Hospital Kuala Lumpur from July 2009 to June 2016. Results. Sixty-two patients were identified, with equal cases involving males and females. Majority of patients were Malays (41.9%), followed by Indians (35.5%), Chinese (17.7%), and other ethnicities (4.8%). Median age at diagnosis was 25 (IQR: 14) years. There is a delay in diagnosis with a median of 24 (IQR: 52) months. Most of the patients had lesions on the axilla (85.5%), followed by groin (33.9%) and gluteal region (29%). Gluteal lesions were more common in males. Nodules (67.7%), sinuses (56.5%), and abscesses (33.9%) were the main clinical features, with 43.5% classified under Hurley stage 2. There was no difference in terms of symptoms and types of lesions among different ethnicities and genders. Majority received systemic antibiotics, more than half had retinoid, and third of the patients had surgical intervention. Conclusions. A prompt recognition of HS is imperative, to screen for comorbidities and to initiate early treatment to reduce physical and psychological complications.